Design Upgrade of Some Selected Evening Gowns as a Sustainable Method in the Fashion Industry - El-jasser, Haifa; Samia, Hassan (International Journal of Fashion and Design, 2023)
Purpose: The study sought to achieve sustainability in the fashion industry through the redesign of outfits for some selected evening gowns. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data, or that which can be collected without field work. Desk research is basically involved in collecting data from existing resource; hence, it is often considered a low - cost technique compared to field work. The study relied on already- published studies, reports, and statistics. This secondary data was easily accessed through online research and the library. Findings: The study's findings revealed statistically significant differences between the mean scores of the direction of measurement of the study sample's opinions, as well as the existence of a correlation between the mean scores of each of the axes in the proposed study's mindset scale. These outcomes prove that the fashion renewal of durable gowns is one of the ways to verify garment sustainability. Unique Contribution to Theory, Practice and Policy: The concept of the circular fashion theory is derived from the broader concept of the circular economy, which aims to reduce waste and extend the lifespan of fashion products. The theory promotes sustainable practices such as up- cycling, refurbishing, and remanufacturing to create new value from existing garments. In other words, it encourages the reuse of materials and products to minimize waste and reduce environmental impact. In addition by applying circular fashion theory, designers can upgrade selected evening gowns by repurposing existing materials, incorporating sustainable textiles, or redesigning elements of the gowns to make them versatile and timeless. This theory encourages a shift from the linear "take-make-dispose" model to a more sustainable and circular approach. By adopting circular fashion practices, we can help create a more sustainable future for the fashion industry. Sustainability could potentially act as an argument for future studies in the fashion and design businesses. The study is expected to benefit policymakers and stakeholders in the fashion business in the Kingdom of Saudi Arabia. The study findings will be used to improve and develop the performance of fashion design sustainability. The study recommends that the adoption of effective fashion design for durable evening gowns will help achieve fashion sustainability.